Pengaruh Model Pembelajaran Student Facilitator and Explaining Terhadap Motivasi Belajar Siswa Kelas IX SMP Negeri 3 Lintong Nihuta Kabupaten Humbang Hasundutan - Sinthia Louisa Hutabarat; Eben H. Telaumbanua; Oktober Tua Aritonang; Senida Harefa; Robinhot Sihombing (Pusat Riset dan Inovasi Nasional, 2023)
The aim of this research is to find out how much the Student Facilitator and Explaining learning model has on the learning motivation of class IX students at SMP Negeri 3 Lintong Nihuta, Humbang Hasundutan district, for the 2023/2024 academic year. The method used in this research is a quantitative method. The population is all class IX students of SMP Negeri 3 Lintong Nihuta, Humbang Hasundutan Regency for the 2023/2024 academic year, totaling 191 people and a sample of 32 people was determined using a purposive sampling technique. Data was collected using a positive closed questionnaire with 35 items. The results of the data analysis show that there is an influence of the Student Facilitator and Explaining learning model on the learning motivation of class IX students at SMP Negeri 3 Lintong Nihuta, Humbang Hasundutan district for the 2023/2024 academic year: 1) Test the analysis requirements: a) positive relationship test obtained with a value of rxy = 0.586 > rtable(=0.05,n=32) = 0.349, thus it is known that there is a positive relationship between variable dk=n-2=30)= 2.042, thus there is a significant relationship between variable 60X. b) Regression coefficient of determination test (r2) = 34.3%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(=0.05, dk numerator k=14, dk denominator=n-2=32-2=30) namely 15.66 > 2.01 Thus Ha accepted and H0 rejected.